Certain Hospital Waste Management Practices in Isfahan, Iran - Ferdowsi, Ali (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Infected hospital wastes are among hazardous wastes, and special treatment methods are needed for their disposal. Having information about present status of medical waste management systems is of great importance in finding weak, and for future planning. Such studies have not been done for most of the hospitals in Iran. METHODS: This paper reports the results of a study on the present status of medical waste management in Isfahan hospitals. A ten page researcher made questionnaire was used to collect data in terms of collection, transportation, segregation, treatment and disposal. For assessment of autoclaves, standard tests including TST (Time, Steam, and Temperature) strip test and spore tests were used. Samples were made of stack gases of incinerators. Quantity and composition of hospital wastes in Isfahan were also measured manually. RESULTS: Of all wastes in selected hospitals, 40% were infected wastes (1.59 kg/day/bed), which is 15 to 20% higher than World Health Organization (WHO) standards. TST and Spore test results were negative in all samples. Stack gases analysis showed high concentration of CO in some samples. Besides, the combustion efficiency in some samples is less than 99.5%, which is the standard criterion in Iran. CONCLUSIONS: This study may create awareness regarding the magnitude of the problem of waste management in hospitals of Isfahan and may stimulate interests for systematic control efforts for hospital waste disposal. Hospital waste management cannot succeed without documented plans, certain equipment, defined staff trainings, and periodic evaluations.